2021
DOI: 10.2147/ijgm.s333904
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ABCC5 Among ATP-Binding Cassette Transporter Family as a New Biomarker for Hepatocellular Carcinoma Based on Bioinformatics Analysis

Abstract: Liver cancer is the fifth most common type of cancer worldwide, and the ATPbinding cassette (ABC) transporter family has been widely accepted as a cause of multidrug resistance. This study was conducted to explore the potential value and mechanisms of the ABC transporter gene family in the liver hepatocellular carcinoma (LIHC). Materials and Methods: Data were collected from different public databases. UALCAN, ONCOMINE, and GEPIA were used to retrieve a selection of differently expressed and pathological stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 41 publications
3
33
0
Order By: Relevance
“…Sepsis, caused by infection, is a syndrome of the systemic inflammatory response 1,32 ; it is usually evaluated by measuring the body temperature, peripheral blood leukocyte count, neutrophil percentage, C‐reaction protein (CRP) levels, 33 and organ function. However, the sensitivity and specificity of these indicators remain poor; our findings further confirmed their low value in evaluating the severity of sepsis and failure to identify patients with potential poor prognoses 34,35 …”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Sepsis, caused by infection, is a syndrome of the systemic inflammatory response 1,32 ; it is usually evaluated by measuring the body temperature, peripheral blood leukocyte count, neutrophil percentage, C‐reaction protein (CRP) levels, 33 and organ function. However, the sensitivity and specificity of these indicators remain poor; our findings further confirmed their low value in evaluating the severity of sepsis and failure to identify patients with potential poor prognoses 34,35 …”
Section: Discussionsupporting
confidence: 55%
“…However, the sensitivity and specificity of these indicators remain poor; our findings further confirmed their low value in evaluating the severity of sepsis and failure to identify patients with potential poor prognoses. 34,35 Nutritional status is closely linked to the prognosis of patients. 36,37 Inadequate nutrition leads to poorer survival outcomes in patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qiu et al Identified ABCC5 as a new biomarker of hepatocellular carcinoma by bioinformatics analysis. 10 Li et al 11 constructed a melanoma prognosis model based on apoptosis‐related genes using bioinformatics. miRNA is a kind of endogenous, non‐coding small molecule RNA that can regulate the expression of target genes and play an important role in cell proliferation, differentiation, apoptosis, angiogenesis, and inflammatory immune response.…”
Section: Discussionmentioning
confidence: 99%
“…For melanoma, which is a tumor with a poor prognosis, the establishment of an effective prognostic model and the exploration of its mechanism of action can improve the macrophages but negatively correlated with the abundance of CD8 + T cells. 19 M1 macrophages exhibit proinflammatory activity and play an antitumor role, while M2 macrophages exhibit anti-inflammatory activity and promote tumor growth. It has been shown that the antitumor effects of immune checkpoint inhibitors can be enhanced by repolarizing M2 macrophages into M1 macrophages, and CD8 T cells located at the melanoma tumor invasive margin can predict the clinical response to PD-1 blockade therapy and are positively correlated with the response to pembrolizumab.…”
Section: Discussionmentioning
confidence: 99%